PEMBERDAYAAN TBM MELALUI DANA BANTUAN DIREKTORAT PENDIDIKAN MASYARAKAT - Bintang Petrus Sitepu (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2012)
Community Reading Centers (CRC) play an important role in developing the community to become a reading and learning society. The Indonesian Government, therefore, encourages the development of CRCs by providing financial assistance or grant to selected CRCs. The problem rised in this research is how the grant influences TBM’s development. This research aims at describing the development of CRCs which had received the grant. The research was done in four districts in Banten Provinces as from June through November 2011 coffering seven CRCs. Applying qualitative paradigm, the research collected data using observation, interview, and study document techniques. The data were analyze qualitatively to draw conclusions and suggestions. The research findings show that the development of CRCs received the grant is not as expected. Based on the findings the research suggest the concerned institutions to intensify monitoring and supervision on the CRCs.